KEPRIBADIAN TOKOH DALAM NOVEL RASA KARYA TERE LIYE - Windha, Windha; Sulissusiawan, Ahadi; Seli, Sesilia (Universitas Tanjungpura, 2024)
This research aims to identify the personalities of the characters in the novel Rasa by Tere Liye. The method used in the research is a qualitative descriptive method, Sigmund Freud's psychoanalytic approach. The source of the data in this study was obtained from the author of the novel Rasa, Tere Liye, and the indirect data source used was in the form of quotations that indicated the character's personality. Documentary research techniques are used in data collection techniques. The main tool of data collection is the researcher himself. The results of the analysis show that (1) the characters and characterizations in the novel, namely using two character painting techniques, namely the expository technique and the dramatic technique (2) the character's personality structure which refers to Sigmund Freud's theory, namely the aspects of the id, ego, and superego. The most prominent personality aspect of each character is the id aspect, so that it is difficult to control oneself (3) the factors underlying personality are seen based on personal aspects, namely biological factors, curiosity motives, love motives, selfesteem motives and needs. search for identity, motives, values, attitudes and emotions.